Rare missense variant p.Ala505Ser in the ZAK protein observed in a patient with split-hand/foot malformation from a non-consanguineous pedigree. Issue 4 (April 2020) - Funk, Christopher Ronald; Huey, Elizabeth S.; May, Melanie M.; Peng, Yunhui; Michonova, Ekaterina; Best, Robert G.; Schwartz, Charles E.; Blenda, Anna V.
Objective: Split-hand/foot malformation (SHFM) is a rare, often debilitating, congenital limb malformation. A single nucleotide polymorphism within the leucine zipper containing kinase AZK ( ZAK ) gene was recently associated with SHFM in two consanguineous Pakistani pedigrees. We hypothesized that additional unrelated patients with the phenotype may carry a pathogenic mutation in ZAK . Methods: DNA samples were collected from 38 patients with SHFM and associated hearing loss for Sanger DNA sequencing and in silico analysis. Results: Two missense mutations within ZAK were detected in 11 patients, but only one missense variant, p.Ala505Ser, occurred with a presumed rare allele frequency. In silico modeling of the ZAK protein with the p.Ala505Ser substitution indicated a negative binding free energy change (mean ΔΔG = −0.9), representing destabilization of the ZAK tertiary structure. Additional laboratory analysis demonstrated a chromosome region 7q21.3-q22.1 deletion. This locus contains the SHFM-1 causative genes SHFM1, DLX5, and DLX6 (distal-less homeobox-5 and -6). Conclusions: We report a novel and rare missense variant, ZAK p.Ala505Ser, in one patient with SHFM from a non-consanguineous pedigree. This variant mildly destabilizes the ZAK tertiary structure. Although this mutation involved a deletion at the SHFM1 locus (7q21.3-q22.1), ZAK signaling destabilization may have contributed to the phenotype, which included hearing loss.